De novo EEF1A2 mutations in patients with characteristic facial features, intellectual disability, autistic behaviors and epilepsy. (29th April 2014) - Nakajima, J.; Okamoto, N.; Tohyama, J.; Kato, M.; Arai, H.; Funahashi, O.; Tsurusaki, Y.; Nakashima, M.; Kawashima, H.; Saitsu, H.; Matsumoto, N.; Miyake, N.
Abstract : Eukaryotic elongation factor 1, alpha‐2 (eEF1A2) protein is involved in protein synthesis, suppression of apoptosis, and regulation of actin function and cytoskeletal structure. EEF1A2 gene is highly expressed in the central nervous system and Eef1a2 knockout mice show the neuronal degeneration. Until now, only one missense mutation (c.208G > A, p.Gly70Ser) in EEF1A2 has been reported in two independent patients with neurological disease. In this report, we described two patients with de novo mutations (c.754G > C, p.Asp252His and c.364G > A, p.Glu122Lys) in EEF1A2 found by whole‐exome sequencing. Common clinical features are shared by all four individuals: severe intellectual disability, autistic behavior, absent speech, neonatal hypotonia, epilepsy and progressive microcephaly. Furthermore, the two patients share the similar characteristic facial features including a depressed nasal bridge, tented upper lip, everted lower lip and downturned corners of the mouth. These data strongly indicate that a new recognizable disorder is caused by EEF1A2 mutations.